On the characterization of bimodal porous carbon via water adsorption: The role of pore connectivity and temperature. (July 2021) - Liu, Lumeng; Zeng, Wenmao; Tan, Shiliang (Johnathan); Liu, Meng; Do, D.D.
Abstract: The behavior of water adsorption on carbonaceous materials is distinct from the simple gases, enabling it as a complementary probe for characterization. Doing so requires a profound understanding of how water adsorbs microscopically. Experimental water isotherms for bimodal micro-mesoporous carbon exhibit a stepwise behavior with two steps for high temperatures and, surprisingly, one step for low temperatures. The two-step behavior and the unusual temperature dependence is worthy of an explanation from microscopic perspective, and to this end we carried out extensive Monte Carlo simulation for water adsorption in a pore model composed of linearly connected micropore and mesopore. Our simulation results show that water molecules could readily fill the micropore section and the prerequisite for the filling of the mesopore section is the existence of a water cluster spanning across the junction between the micropore and the mesopore at 298 K. Temperature is another important factor and stronger thermal fluctuations at higher temperatures facilitate the advancement of the interfaces of adsorbed water thus making filling in mesopore happen even without the formation of the PSC at high temperatures ( e.g ., 450 K). The findings in this paper offer useful insights on the characterization of bimodal porous carbon via water adsorption. Graphical abstract: Image 1 Highlights: Connectivity is critical for the filling of small mesopores with water molecules. Water adsorption in micropore section precedes that in mesopore section. A pore-spanning cluster at the junction is pivotal for mesopore section. Thermal fluctuation affects expansion of H-bond network of water cluster.